Efektifi vitas Lokasi dan Waktu Injeksi Insulin Terhadap Pengendalian Kadar Gula Darah 2 Jam Setelah Makan pada Penderita Diabetes Melitus - Santosa, Agus (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background: One of the methods to control blood sugar level within 2 hours after eating in patients with diabetes mellitus is by providing proper insulin injection (proper dose, proper method, proper time and proper location)Objective: To determine the eff ective locationand time of insulin injection on the control of blood sugar level within 2 hours after eating in patients with diabetes mellitus.Method: This is an experimental research with the design of randomized complete block design (RCBD). Patients with IDDM type of Diabetes mellitus in Bantul Regency became the population in this research; meanwhile the samples used were 60 respondents taken by Simple Random Sampling and they were divided into 4 blocks. The respondents were injected by using analogue type insulin with daily dose on four sites (abdominal, deltoid, thighs, gluteus) and time of the provision (0, 10, 20 and 30 minutes before eating). The blood sugar level within two hours after eating was measured by using a glucometer.Result: The result of the analysis of two-way ANOVA and Tukey HSD indicates that there is a diff erence in blood sugar level within two hours after eating in patients with diabetes mellitus to whom insulin injection is performed on abdominal, deltoid, thigh and gluteus location (p= 0.000). There is a diff erence in blood sugar level within two hours after eating in patients with diabetes mellitus to whom insulin injection is performed within 0,10,20 and 30 minutes before eating (p= 0.000). The most eff ective location and time for insulin injection is in the abdomen in 0 minutes before eating.Conclusion: Insulin injection which is performed on abdominal location in 0 minute is eff ective to control blood sugar level within two hours after eatingKeywords: Location, Time, Insulin Injection